ADVENTURE SPORTS: AN OPTION OF LEISURE AND DEVELOPMENT FOR THE CITY OF AREIA - PB (Fiep Bulletin - online, 2011)
In broad terms, this study is aimed at analyzing the potentialities and difficulties of adventure sports in the city of Areia – PB as an opportunity for leisure and local development. In order to reach these goals, we chose to use in this quality research an investigation method. This work was developed in the city of Areia – PB, and its sample was selected by uniqueness, convenience and availability; and composed of municipal secretaries and local tourism guides. It was possible to find in Areia many rich natural beauties, such as the fauna and the flora, waterfalls, stone walls, natural pools, trails, native forests (mainly represented by the Parque Estadual Mata do Pau Ferro), sugarcanes, dams and mills. The area demonstrates that Areia is a place where people can practice trekking, Mountain Bike, Downhill, horseback riding, 4x4 vehicles rides, Motocross, climbing, rappelling, going to waterfalls, contemplative diving, canoeing, tree climbing and zip line. However, all this potential has not been enjoyed as it should have been for many different reasons. Considering all that was said in the interviews, and then analyzed and discussed, we assume that the key problem to be solved refers to the knowledge about leisure and its importance to the development polices.
Keywords: Adventure sports; leisure; development